Penerapan Model Pembelajaran Inquiry Based Learning untuk Meningkatkan Aktivitas dan Hasil Belajar Kognitif Siswa - Kadiwone, Lukas Liku; Dharmawibawa, Iwan Doddy; Utami, Septiana Dwi (Bioscientist : Jurnal Ilmiah Biologi, 2022)
This study aims to increase the activity and cognitive learning outcomes of students through the application of the Inquiry Based Learning model. This type of research is Classroom Action Research (CAR). The subjects in this study were all seventh grade students of SMP Negeri 5 Mataram in the 2021/2022 academic year. The instruments used in this study were lesson plans implementation sheets, student activity observation sheets, and student cognitive learning outcomes tests. The results showed that the implementation of the lesson plan increased in the first cycle of the first meeting reaching 80.98%, at the second meeting it reached 85.71% with a very good category. The implementation of the lesson plans in the second cycle of the first meeting reached 80.71%, and at the second meeting it reached 90.47% with a very good category. The student activity sheets in the first cycle reached 55% with a fairly good category, while the student activity sheets in the second cycle reached 72% in the good category. The results of the student’s cognitive learning test in the first cycle obtained an average value of 56 with a classical completeness score achieved 40% in the incomplete category. The test of students’ cognitive learning outcomes in the second cycle obtained an average value of 77, with the classical completeness score achieved 90% in the complete category. Thus, it can be concluded that, there is an increase in the activity and cognitive learning outcomes of students through the application of the Inquiry Based Learning learning model.